Retrofitting of Skyscraper Building By Using Time History Analysis - Shubham Singh, Barkha Verma (Mathematical Statistician and Engineering Applications, 2023)
A skyscraper is a multi-story structure that is tall and constantly habitable. Originally, the word referred to a structure of at least 35-50 stories that was mostly utilized for office, commercial, and residential functions. A skyscraper is sometimes known as a high-rise; however, the term skyscraper is generally reserved for structures taller than 50 meters. Skyscrapers frequently have a steel structure that supports curtain walls. Instead of load-bearing walls, these curtain walls are either supported by or hung from the framework above earthquake is a major natural disaster in which many structures are damaged or collapse due to unacceptable or improper seismic motion design. The nation’s economy and pace of growth are both impacted by earthquakes, so it is imperative that effective preventative measures are created for the benefit of both the people and the country.In this study, several retrofitting technologies, such as bracing, shear walls, and infill walls, are applied for symmetrical G+40 high-rise buildings. The same structural properties were used to create 4 different sorts of models. Time history analysis is used in seismic analysis to take varying ground motion intensities into account. In order to determine the optimum retrofitting for the structure, the findings of the analysis are compared.